Evaluating the effect of various treatments on the diatom Haslea ostrearia for achieving axenic cultures - Khiar, F.; Gabed, N.; Lamara, S. A. C.; Abi Ayad, S. M. E. A. (Regulatory Mechanisms in Biosystems, 2024)
Axenic microalgae cultures are needed for several applications: genetic research, chemical exploration, aquaculture, and the study of interactions between microalgae and bacteria. Eliminating bacterial contamination while preserving the vitality of microalgae remains a considerable challenge. In this study, we focused on Haslea ostrearia (Simonsen, 1974), a highly coveted diatom known to produce the valuable blue pigment "marennine", responsible for oyster greening. To establish axenic cultures of the diatom H. ostrearia, we cultivated the strain NCC 527 (HoB4) in ASW medium at 19 °C with a 16-hour light and 8-hour dark photoperiod. Various treatments were tested: sonication, centrifugation, filtration, the use of detergent, and antibiotics. We evaluated the diatom response to these treatments and estimated the elimination of bacterial contamination. The results showed that physical treatments were moderately efficient. The sonication treatment effectively eliminated bacterial aggregates, but it also affected cell survival; 15 minutes of sonication reduced bacterial aggregates, but only 21.6% of cells remained motile and alive. Repeated centrifugation two times for 10 minutes allowed a moderate 49.9% reduction of bacteria. Treatment with Triton-X100 had a lethal effect on H. ostrearia. Filtration treatments decreased bacterial contaminants by only about 5%. We performed an analysis of variance (ANOVA) to compare diatom densities after treatments and bacterial removal. We also investigated the diatoms’ growth after physical treatments and performed a comparison test between densities according to culture days. Repeated centrifugation and supernatant renewal appear to be less aggressive treatments on the diatom, with high bacteria removal without severely impacting the diatom cell density or growth. However, these physical treatments were not enough to produce total bacterial elimination. Combining antibiotic treatment with centrifugation and rinsing proved to be more effective, decreasing bacterial contamination while preserving diatom cells. We controlled the removal of bacterial contamination by using molecular techniques targeting 16S rRNA, along with colony counting and liquid medium inoculation. This work establishes the foundation for the development of an optimal protocol for H. ostrearia axenic culture in the future.